2021
DOI: 10.1001/jamasurg.2020.5050
|View full text |Cite|
|
Sign up to set email alerts
|

Anterior Approach vs Conventional Hepatectomy for Resection of Colorectal Liver Metastasis

Abstract: IMPORTANCETumor relapse after partial hepatectomy for colorectal liver metastasis (CRLM) remains an unsolved issue. Intraoperative manipulation of the liver during conventional hepatectomy might enhance hematogenous tumor cell spread. The anterior approach is an alternative approach that may reduce intraoperative tumor cell dissemination.OBJECTIVE To determine the efficacy and safety of the anterior approach compared with conventional hepatectomy in patients undergoing resection for CRLM. DESIGN, SETTING, AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
1
16
2
Order By: Relevance
“…In the present analysis, all included patients underwent routine thromboprophylaxis. Of note, the rate of clinically relevant posthepatectomy hemorrhage was found to be comparable to other studies [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…In the present analysis, all included patients underwent routine thromboprophylaxis. Of note, the rate of clinically relevant posthepatectomy hemorrhage was found to be comparable to other studies [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, any patients who underwent liver resection combined with radiofrequency or microwave ablation were excluded [ 12 ]. Although the anterior approach was used during minimally invasive major hepatectomy, both anterior and posterior approaches were used during open procedures [ 13 ]. Although the safety of concomitant liver resection and colorectal resection has even been shown in robotic-assisted patients, those who underwent simultaneous colorectal surgery were not included in any of the 3 groups [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…[8] Hepatectomy is currently the most reliable; hepatectomized patients can now achieve long-term survival. [9] However, recurrence has been reported in 50% to 80% of hepatectomized patients, with remnant liver recurrence being the most common and representing approximately half of all recurrences. [10] Ultrasound-guided radiofrequency ablation (RFA), as a common minimally invasive treatment modality, has been widely used in clinical practice for the local control of liver tumors, and previous reports have demonstrated that thermal ablation had an advantage over surgical resection in being less invasive for hepatocellular carcinoma [11,12] ; therefore, it can also be an alternative option for patients with unresectable CRLM.…”
Section: Introductionmentioning
confidence: 99%